CRITICAL PERSPECTIVES ON BLACK FAMILY THEORY: A REVISED ABC-X MODEL FOR UNDERSTANDING BLACK FAMILY STRESS AND BLACK FAMILY STRENGTHS - Toliver, Susan D. (European Scientific Journal, ESJ, 2015)
Based on a study of Black corporate managers and their families it was discovered that existing models of family stress were incomplete, or inadequate in their ability to help us understand the nature of stress for these families and how that stress is managed, and, the coping resources available to these families with which to do so. Existing models are limited for Black families in that they do not take into account the pervasiveness of racism in the life experience of these families, nor do they include the traditional/historical strengths for survival of black families that can function as crisis meeting resources. An alternative conceptualization of McCubbin and Patterson’s (1981,1982,1983) Double ABCX Model, a revision of Reuben Hill’s (1965) ABCX Model, incorporating racism, and, the five traditional Black family strengths identified by Robert Hill (1971) is suggested. It is argued that the inclusion of racism in understanding the nexus of Black family stress and the traditional Black family strengths that enable Black families to cope with the stresses associated with work would be most useful. Discussion of differences by race and sources of stress with emphasis on Black families, and examples of the persistence of racism for Black corporate families will be provided. Discussion of the uses and value of traditional Black family strengths, including examples, will be given. Black corporate families are defined as a subset of Black upper middle to upper class families whose life experiences are similar to those of other Black same class families.